2D statistical models of facial expressions for realistic 3D avatar animation - Zalewski, L.; Gong, S. (2005 IEEE Computer Society Conference on Computer Vision and Pattern Recognition (CVPR'05), 2005)
We address the issue of modelling facial expressions for realistic 3D avatar animation. We introduce a hierarchical decomposition of a human face into different components and model them according to their intrinsic functionalities. The parametrisation of the expressions is achieved in a two-level framework. First level accounts for the low level component facial actions and is represented by hierarchical latent variable models. The second level models the final expressions as a combination of subcomponent information extracted from the lower level using combinatorial logic. Finally we produce continuous animation curves that are used to animate 3D avatar in a morph-based fashion. Our approach is entirely based on 2D information extracted from the input source.